Suboptimal COVID‐19 vaccine uptake among hospitalised patients: an opportunity to improve vulnerable, hard‐to‐reach population vaccine rates. Issue 10 (27th August 2022) - Roberts, Matthew B.; Ferguson, Catherine; McCartney, Erin; Selvanderan, Kendra; Badiei, Arash; Paradiso, Lisa; Wallace, Caitlin; Torpy, Helena; Zhang, Frank; Sim, Beatrice; Papanicolas, Lito; Ashokan, Anushia; et al.
Abstract: Background: COVID‐19 vaccination represents a key preventative part of the Australian public health approach to the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic. Hospital inpatients are frequently high risk for severe COVID‐19 and death. Anecdotes of high‐risk inpatients being unvaccinated and a lack of electronic medical record (EMR) visibility of COVID‐19 vaccination status prompted the present study as these patients could represent a risk to themselves, staff, other patients and service provision. Aims: To determine the uptake of COVID‐19 vaccine among inpatients at an adult Australian tertiary public hospital and identify reasons for non‐vaccination. Methods: A point‐prevalence study of patient‐reported COVID‐19 vaccine status was conducted on 26 October 2021 through an in‐person interview with collection of demographic factors and reasons for non‐vaccination. Results: Of 368 (68% of inpatients) participants, 280 (76%) reported receiving at least one COVID‐19 vaccine dose. Vaccination status was associated with older age, having received the flu vaccine, being born in Australia and not requiring an English‐language interpreter. The majority (88%) of participants had at least one comorbid risk factor for severe COVID‐19. Of the unvaccinated ( n = 88), 67% were willing to be vaccinated with 54% of those indicating vaccination in hospital would be helpful and 42% requesting approval from their doctor. Conclusions: Vaccine uptake in our cohort is suboptimal. Existing public health programmes have failed to reach this high‐risk, vulnerable population. Changes to the national vaccination strategy to include a parallel inhospital programme for all hospital encounters and target culturally and linguistically diverse individuals might improve uptake among this high‐risk, hard‐to‐reach group of patients.